Modernizing Mental Health: The Role, Ethics, and Competencies of Counseling in the Digital Age - Syifa Nurul Maola; Fitri Andela; Rifa Alifah Salsabila; Nazwa Syifa Syairani; Annisa Dwi Rizqia; Popy Mayasari Afendy (Ma'soem University, 2025)
This article critically re-examines the modernization of counselling in the digital age, arguing that technology is not merely an auxiliary tool but a disruptive force that threatens to redefine the foundations of therapeutic practice. Using a systematic literature review, 38 primary sources were analysed: 31 peer-reviewed journal articles, 4 academic books, and 3 professional guidelines selected through PRISMA-based screening from Google Scholar, ScienceDirect, and ResearchGate (2008–2025). The findings indicate that tele-counselling, counselling applications, and AI-assisted interventions significantly expand access and offer flexible, data-driven mental health support. However, the evidence also reveals an ethical paradox: while digital platforms claim to democratise psychological services, they simultaneously increase vulnerability to privacy violations, algorithmic bias, and emotional disconnection. Particularly for adolescents, technology-mediated counselling correlates with emerging risks, including social media addiction, cyberbullying trauma, and digital isolation that paradoxically require the very counselling services the platforms aim to provide. These results challenge the assumption that technological innovation inherently improves counselling outcomes and suggest that the profession may be approaching a critical inflexion point: counsellors must develop digital competencies or risk being replaced by artificial systems incapable of empathy. The study concludes that technology can strengthen mental health services only if strict ethical safeguards, digital literacy, and a reaffirmation of the therapeutic alliance as the non-negotiable core of counselling guide its integration.